2010
DOI: 10.1051/vetres/2010041
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based transcriptional profiling ofEimeria bovis-infected bovine endothelial host cells

Abstract: Within its life cycle Eimeria bovis undergoes a long lasting intracellular development into large macromeronts in endothelial cells. Since little is known about the molecular basis of E. bovis-triggered host cell regulation we applied a microarray-based approach to define transcript variation in bovine endothelial cells early after sporozoite invasion (4 h post inoculation (p.i.)), during trophozoite establishment (4 days p.i.), during early parasite proliferation (8 days p.i.) and towards macromeront maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Such mechanism would enable continuation of the parasite development even under fully active immunity of the host. It was shown that Eimeria parasites are able to compromise signalling and modulate gene expression of the host in order to support their development (del Cacho et al, 2004;Taubert et al, 2006Taubert et al, , 2010Fetterer et al, 2007;Guo et al, 2013;Schmid et al, 2014). If such immune evasion is an important determinant of the host specificity, it would be not surprising that the pattern of host specificity is not reflected in the phylogenetic tree of Eimeria.…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanism would enable continuation of the parasite development even under fully active immunity of the host. It was shown that Eimeria parasites are able to compromise signalling and modulate gene expression of the host in order to support their development (del Cacho et al, 2004;Taubert et al, 2006Taubert et al, , 2010Fetterer et al, 2007;Guo et al, 2013;Schmid et al, 2014). If such immune evasion is an important determinant of the host specificity, it would be not surprising that the pattern of host specificity is not reflected in the phylogenetic tree of Eimeria.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro accessibility and mass production of E. bovis meronts II is of particular scientific interest for numerous reasons since (i) it allows for studies on merozoite II-host cell interactions which, as demonstrated for E. bovis sporozoite infections, are likely to be multifactorial and to rely on several regulatory processes to guarantee parasite replication Lang et al 2009;Taubert et al 2010;Ruiz et al 2010;Lutz et al 2011;Hermosilla et al 2012);(ii) there is some evidence that meronts II represent the major targets for the protective immune response in animals immune to Eimeria spp. infections (Rose et al 1992a, b;Shi et al 2001a, b;Taubert et al 2008;Hermosilla et al 2014); (iii) these cultures are useful for the screening of pharmaceutical, immunological, or biochemical compounds against Eimeria (Hamid et al 2014;Silva et al 2015); and (iv) it offers the possibility to perform stage-specific analyses at the proteomic or transcriptomic level as demonstrated for E. bovis sporozoiteinfected host cells Lutz et al 2011).…”
Section: Gm-csfmentioning
confidence: 99%
“…BCL2L14 expression is markedly up-regulated in CD4 + T-cells from patients with the autoimmune disorder, systemic lupus erythematosus (SLE) and several lines of evidence implicate this dysregulation in pathogenesis (Luo et al, 2009). Dysregulated expression of BCL2L14 in mammalian cells has also been noted in response to infection with a variety of pathogens (Flori et al, 2008;Mehra et al, 2010;Balas et al, 2011;Singh et al, 2011;Taubert et al, 2010;Almeida et al, 2012;Wang et al, 2012), indicative of a role in innate immunity.…”
Section: Identitymentioning
confidence: 99%
“…Studies with murine cells have further shown that exosomes derived from macrophages infected with Mycobacterium tuberculosis can block the activation of a subset of interferon-Îł inducible genes, including BCL2L14, which may serve to suppress the host innate immune response beyond the site of infection (Singh et al, 2011). BCL2L14 is one of several Bcl-2 family members that is dysregulated in bovine endothelial cells following infection with the parasite Eimeria bovis (Taubert et al, 2010). It is markedly upregulated in human alveolar macrophages within a few hours of infection with H1N1 influenza A virus PR/8 (Wang et al, 2012) and it is also induced following the infection of human monocyte-derived dendritic cells with wild type Dengue 3 virus (a Flavivirus) or the chimeric CYD3 vaccine virus (Balas et al, 2011).…”
Section: Notementioning
confidence: 99%